2017
DOI: 10.1371/journal.pone.0179987
|View full text |Cite
|
Sign up to set email alerts
|

Urban-rural differences in disability-free life expectancy in Bangladesh using the 2010 HIES data

Abstract: BackgroundResearch on health expectancy has been carried out in Bangladesh but none of it has examined the differences in Disability-Free Life Expectancy (DFLE) between urban and rural setting in context of rapid urbanization of Bangladesh in past decades.ObjectivesThe present study aims to estimate DFLE for people of all ages living in urban and rural areas in Bangladesh, and to examine the differences in DFLE between these two areas.MethodsData from the Sample Vital Registration System 2010 and the Banglades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…This finding needs to be interpreted with the fact that more respondents with higher secondary level education were living in rural areas while higher educated respondents were living in urban and city corporation areas. The housing pattern of the rural and urban areas is structurally different ( 41 ), and urban housing in Bangladesh lacks the comfortability for the older people. This finding is supported by the findings that the respondents living in urban areas had lower household preparedness.…”
Section: Discussionmentioning
confidence: 99%
“…This finding needs to be interpreted with the fact that more respondents with higher secondary level education were living in rural areas while higher educated respondents were living in urban and city corporation areas. The housing pattern of the rural and urban areas is structurally different ( 41 ), and urban housing in Bangladesh lacks the comfortability for the older people. This finding is supported by the findings that the respondents living in urban areas had lower household preparedness.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are some arguments that people living in urban areas are wealthier than those living in rural areas, in terms of housing, education, income, health facilities, sanitation, and a lower rate of disability [28]. Islam et al [7] conducted research on the disability-free life expectancy of the urban-rural elderly in Bangladesh, and they confirmed the above argument and found that there were distinct inequalities in LE, DFLE, and LE with disability (DLE) between rural and urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of research so far has focused on disability-free life expectancy (DFLE), because of the wider availability of appropriate survey data recording this information. Although many studies have reported DFLE in individual LMICs (Brønnum-Hansen, Duraidi, Qalalwa, & Jeune, 2015; Eguez-Guevara & Andrade, 2015; Islam et al, 2017; Lau, Johnson, & Kamalanabhan, 2012; Luo et al, 2016; Moreno et al, 2018) or cross-country comparison (Payne, 2018), few have comparable data across countries and estimated the prevalence of disability using a consistent study design and measurement methods. Previous studies using the World Health Organization Study on Global Aging and Adult Health (SAGE) and the Survey on Health, Well-Being, and Aging in Latin America and the Caribbean (SABE) have suggested variations in DFLE across older adults from various LMICs and highlighted gender differences, where women spent more time in disability than men (Chirinda & Chen, 2017; Minicuci et al, 2011).…”
mentioning
confidence: 99%